Effect of the type of application of Newcastle disease virus on the Ehrlich ascites tumor - Milanez, Tomaž (Radiology and oncology (Ljubljana), 1996)
Newcastle disease virus (NDV) has been shown to have an inhibitory effect on the tumours. Most authors use peritumoral application of virus. The purpose of our studz was to compare the effects of the ip in contrast to sc application of the virus on the ip and sc transplanted Ehrlich ascites tumor (EAT) in CBA/H mouse. We measured the length of survival, the tumor cure rates, the metastatic rate, and the frequencz of ascites and sc tumors in the site of ip EAT injection. Prolongation of survival after the therapy with NDV in ip transplanted EAT average time of survival in control group was 70.5 days, and 107 and 79.9 days with ip and sc NDV virus therapy respectively. The differences were significant only between control group and the group treated with ip application of NDV. Tumor cure rates were: ipNDV group 30%, scNDV group 20% and control group 5%. NDV therapy in sc transplanted EAT prolonged the time of survival; in control group it was 63.3 days, and 75.2 and 65.9 days with ip and sc NDV therapy respectively. NDV therapy inhibited metastatic rate of ip transplanted EAT. Inhibition was more effective with ip application of NDV. VIrus therapz also lowered the frequencz of appearance of ascites and sc tumour in the site of ip EAT injevtion. In sc transplanted EAT ip application of NDV inhibited the metastatic rate while in sc applied NDV some stimulation of metastasation was found. Ip application of NDV was found to be superior in contrast to sc application in all its therapeutic effects against EAT. Our results show that the tumor inhibition of NDV, in the system we used, has the characteristics of the biological response modifiers.
Keywords: fiziologija; medicina; miši; rak (medicina); tumor; virusne bolezni